2018
DOI: 10.17576/jsm-2018-4703-22
|View full text |Cite
|
Sign up to set email alerts
|

FeCl3-Activated Carbon Developed from Coconut Leaves: Characterization and Application for Methylene Blue Removal

Abstract: In this study, coconut leaves were used as a starting material for the production of activated carbon by thermal carbonization using FeCl 3 -activation method. Dalam kajian ini, daun kelapa telah dipilih sebagai bahan pemula bagi penghasilan karbon teraktif melalui penkarbonan haba dengan menggunakan FeCl 3 sebagai agen pengaktif. Pencirian karbon teraktif (FAC) dianalisis dengan menggunakan mikroskop elektron imbasan (SEM), transformasi Fourier inframerah (FTIR) dan analisis elemen (CHNS-O). Beberapa parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(25 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…The result for adsorptive removal of MB with respect to adsorbent dosage is displayed in Figure 6. It is apparent that the percentage removal of MB increases rapidly with increase in the dosage of ATBP due to the greater availability of the exchangeable sites or surface area [55,56]. In present work, the highest level of MB removal was achieved using 0.08 g/100 mL ATBP dose and thereafter, further increase in adsorbent dosage did not exert an appreciable increase in the MB removal percentage.…”
Section: Effect Of the Adsorbent Dosagementioning
confidence: 44%
“…The result for adsorptive removal of MB with respect to adsorbent dosage is displayed in Figure 6. It is apparent that the percentage removal of MB increases rapidly with increase in the dosage of ATBP due to the greater availability of the exchangeable sites or surface area [55,56]. In present work, the highest level of MB removal was achieved using 0.08 g/100 mL ATBP dose and thereafter, further increase in adsorbent dosage did not exert an appreciable increase in the MB removal percentage.…”
Section: Effect Of the Adsorbent Dosagementioning
confidence: 44%
“…It was therefore concluded that H 2 SO 4 -activated carbons from coconut leaf is a good precursor for AC preparation in the remediation MB dye from aqueous solution. Similarly, thermal carbonization via FeCl 3activation was used to prepare activated carbon from coconut leaves [112]. The characterization studies were investigatedby bulk density, moisture content, ash content, pH pzc , iodine test, elemental (CHNS-O) analysis and other spectroscopic analyses.…”
Section: Carbonaceous Adsorbents (Such As Carbonized Materials Activmentioning
confidence: 99%
“…Recently, many researchers have looked into modifying the surface of adsorbents for total or complete removal of various dyes from the aqueous solution and generally reported that modifying agents increase the adsorption site(s) for both cationic and anionic dyes. Examples includes: guava leaf [39] bamboo [40,41], plant leaf [42], coconut leaves [43,44], kola nut and bean husk [45,46], ficus racemosa [47,48], Prunus Dulcis [49], durian Leaf [50], dead Leaves of plane trees [51], prunus dulcis [49], Moringa oleifera leaf [52,53], C. camphora leaves [54], berry leaves [55], Glossogyne tenuifolia leaves [56]. Several authors have demonstrated the peculiarity of agricultural-based materials to remove various dyes having diverse molecular structures.…”
Section: Introductionmentioning
confidence: 99%